2003
DOI: 10.1046/j.1365-2400.2003.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine fish life history strategies: applications to fishery management

Abstract: The life history traits of 42 marine fish species were grouped according to the theoretical classifications of life history strategies. This provides a conceptual framework of management options, because life history strategies are the underlying determinants for population responses to climate and ocean changes, they can be used to classify typical population responses. When faced with providing management advice for species for which there is no information on absolute or relative biomass, such as newly expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
239
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(248 citation statements)
references
References 33 publications
6
239
0
3
Order By: Relevance
“…Fishery resources associated with seamounts are particularly susceptible to disturbances caused by fluctuations in environmental conditions and fishing pressure (Pitcher et al 2007). One of the reasons for this high vulnerability is related to the k-strategy (slow growth rate, high longevity, late maturity and low fecundity) (King and Mcfarlane 2003) shown by the majority of the species that occur on seamounts, making them extremely sensitive to fishing exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Fishery resources associated with seamounts are particularly susceptible to disturbances caused by fluctuations in environmental conditions and fishing pressure (Pitcher et al 2007). One of the reasons for this high vulnerability is related to the k-strategy (slow growth rate, high longevity, late maturity and low fecundity) (King and Mcfarlane 2003) shown by the majority of the species that occur on seamounts, making them extremely sensitive to fishing exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…In marine ecosystems, the well-publicized declines of large predatory fishes (4,5) suggest that similar trends may also be common in the sea. However, research to date has found or proposed a wide range of life-history characteristics that cause high vulnerability, including large body size (6)(7)(8)(9), late maturity (6,9), long lifespan (6,(8)(9)(10)(11), low fecundity and high parental investment in offspring (11,12), or high trophic level (2,13). Understanding which traits, or combinations of traits, are most useful for predicting vulnerability has been difficult because analyses have been limited to regional comparisons or narrow species groups, and because reliable global data have not been available to more broadly test which types of fishes are most likely to suffer fisheries collapse.…”
mentioning
confidence: 99%
“…Contemporary approaches to inform stock vulnerability or status for data-poor situations take the form of state indicators (Garcia and Staples 2000;Jennings 2005), qualitative risk assessments (Stobutzki et al 2001), and inferences about vulnerability based on life history characteristics (Musick et al 2000;King and McFarlane 2003). Such approaches strive to apply transparent protocols to simple or limited data.…”
mentioning
confidence: 99%